Pilates versus resistance exercise on the serum levels of hs-CRP, in the abdominal circumference and body mass index (BMI) in elderly individuals - Pestana,Maria Dida Silva (2016)
Recent studies have shown that the elderly exhibit a subclinical state of inflammation associated with increased adipose tissue and several comorbidities. To compare the effects of mat Pilates based exercises and resistance exercise on the serum levels of reactive C protein of high sensitivity (hs-CRP), in the abdominal circumference (AC) and the body mass index (BMI) in the elderly. It is a randomised clinical trial with a sample of 78 elderly individuals (median age 69 years). The active independent variable investigated was nature of treatment intervention (Pilates mat based exercises vs resistance exercise), and the dependent variables were hs-CRP level, AC and BMI. The statistical analysis used Wilcoxon signed rank and Mann-Whitney tests. The correlation between the continuous variables was assessed using Spearmans coefficient of correlation. The data were analysed using SPSS software version 17.0, and probability values lower than 5% (p< 0.05) were considered statistically significant. Mat Pilates based exercises exhibited reductions in serum hs-CPR level (Wilcoxon signed rank test; z = -2.466, p = 0.01), BMI (Wilcoxon signed rank test; z = -3.295, p = 0.001) and AC (Wilcoxon signed rank test; z = -3.398, p = 0.01). Mat Pilates based exercises promoted a significant reduction of the serum hs-CRP levels and anthropometric measurements in elderly individuals.